(untitled) (Journal of Hama University, 2024)
The study aimed at recognizing the level of positive thinking and academic compatibility among the students of the Faculty of Social Sciences, identifying differences according to the academic year, specializing in positive thinking and academic compatibility, and identifying the relationship between positive thinking and academic compatibility and predicting academic compatibility through positive thinking. The study followed the descriptive curriculum (associative-comparative). Positive Thinking, Translation of Wakad (2012), Academic Consensus, Shaheen (2010). The study sample consisted of 271 students from the Department of Social Service in Specialization (Social Service - Media) and in the first-second year of the academic year 1443 AH - 1444 AH. The study showed that the level of positive thinking and academic compatibility is high among social service department students per year (first-fourth) of the Faculty of Social Sciences, and there are statistically significant differences in positive thinking according to specialization in the direction of social service specialization while there are no statistically significant differences according to the school year, There are statistically significant differences in academic compatibility according to the academic year towards the second year and according to specialization towards the specialization of social service There is also a statistical correlation between positive thinking and academic compatibility among students of the Faculty of Social Sciences, and academic compatibility can be predicted by students’ grades on the positive thinking scale. Keywords: Positive thinking - academic compatibility.